The life and labour of 'illegal' and deportable people: undocumented Zimbabwean migrants living and working in Witbank, South Africa - Machinya, Johannes (My University, 2019)
This study is based on ethnographic research among undocumented Zimbabwean migrants living and working in Witbank, South Africa. It explores and analyses the existential and juridical condition of migrant 'illegality' by examining how state enforcement of immigration laws helps to constitute a pervasive sense of 'illegality' and deportability, which is the state of living with deportation as a ubiquitous possibility for undocumented migrants, even if not actually effected. Migrant 'illegality' is produced at the intersection of state efforts to make migration flows legible or readable to the state and migrants' attempts to deal with the state's ability to control migration flows, which highlights the dialectical relation in and adds nuance to the theorisation of the production of migrant 'illegality' and deportability. Deportability inundates undocumented migrants' lives with anxiety and uncertainty over the indeterminacy of the materialisation of actual arrest and deportation. This is markedly characterised by undocumented migrants' inability to determine with certainty what might (or might not) happen to them in their encounters with the regime of immigration law enforcement, whether they would be arrested and deported, or not. This indeterminacy and uncertainty speak to the temporal irregularity that emerges from the unpredictability of arrest and deportation. The threat of deportation registers a vivid awareness among undocumented migrants that one day they will get deported and this translates into a hideous form of anticipatory anxiety over the possibility of something happening without needing it to happen -deportation. I argue that living fearfully anticipating, although without hankering for, the materialisation of actual deportation provides a pervasive sense of 'waiting' for eventual deportation. By underlining the anxieties and uncertainties that emanate from the possibility of deportation, I show how the awareness of being 'illegal' and deportable shapes the everyday lives and work experiences of undocumented migrants. I argue that migrant 'illegality' as well as the threat and fear of deportation are powerful determining conditions that write themselves enduringly into the fabric of undocumented migrants' everyday lives and significantly alter the pattern of their everyday existence and work experiences. This thesis thus also focuses on the sociotemporal implications of living and working under the constant threat and expectation of deportation, which reminds undocumented migrants that their time in South Africa is ephemeral and indefinitely terminable; and this fear infiltrates and shapes undocumented migrants' everyday lives and work experiences. The thesis further looks at undocumented migrants' responses to the challenges that emanate from being 'illegal' and deportable in the face of such adversity. I demonstrate how the responses oscillate between visibility, and therefore engaging directly with state officials on the one hand, and social non-visibility or undetectability on the other, with migrants avoiding interactions with state officials who possess powers to arrest and deport those migrants who are in violation of the country's immigration law.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree of Doctor of Philosophy, University of the Witwatersrand, Johannesburg
Keywords: Undocumented migrants; Immigration enforcement; Illegal migration